PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KREATIF PADA PEMBELAJARAN TEMATIK SISWA KELAS V SD SWASTA HKBP PAGAR JATI - Sihaloho, Lisna Maya Sari; Malinda, Leni; Harahap, Syarifah Ainun (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2024)
The purpose of this writing isto determine the effect og problem based learning(PBL) learning model on creative thinking skill in the tematic learning theme e subtheme 2 class v of SD HKBP Pagar Jati,Lubuk Pakam district. The author chose the problem based learning (PBL) learning model because student are given the opportunity to developthe ability to think creatively in the learning process.in this writing,the author uses the one grup pretest posttest design writing design. The result obtained from the t-test obtained a value of 69.39.with a frequency(db) of 23-2 =21,at the 5 % significance level,the result is 1.721.so we get tcount or >table or 69.39>1.721.then has is accepted and H0 is rejectd,wich means that the hypotesis in this writing is accepted,namely that there is an influence of problem based learning(PBL) learning model on the ability to think creatively in the tematic learning theme 2 subtheme 2 in class v of SD HKBP Pagar jati private elementry school,Lubuk pakam district.